Pedicled myocutaneous trapezius flap for chronic osteomyelitis of the spinous processes - a case report - Vodička, Petr; Mařík, Vladimír (Acta chirurgiae plasticae, 2024)
Complex injuries to the posterior trunk can still pose a significant challenge to the reconstructive surgeon. Due to the lack of skin laxity, dependent anatomical location and the importance of the deeper structures, a systematic approach tailored to the individual defect should be considered for these types of reconstructions. In our case report, we present a reconstructive solution of a chronic defect of the back caused by resection of an ulceration. What was previously considered to be a relapse of a malignant melanoma turned out to be a chronic osteomyelitis of the spinous processes of the thoracic vertebrae. The defect after the resection of the ulceration and infected spinous processes of the thoracic vertebrae with exposed dorsal lamina was covered with pedicled myocutaneous flap. Reconstruction yielded well-vascularized tissue that provided sufficient volume and tissue quality. Even in the light of modern perforator flaps, local or locoregional muscle and myocutaneous flaps remain the first choice for the treatment of deep back defects. Considering all the factors in the given case, plastic surgeons are able to tailor the reconstructive technique to every individual case to match the desired reconstruction goal.
Keywords: Staphylococcal Infections; Dermatologic Surgical Procedures; Back; Humans; záda; Melanoma, Cutaneous Malignant; stafylokokové infekce; Aged; senioři; lidé; Ulcer; Surgical Flaps; maligní melanom kůže; Postoperative Care; Male; Osteomyelitis; pooperační péče; chirurgické laloky; osteomyelitida; vřed; hrudní obratle; mužské pohlaví; Thoracic Vertebrae; dermatochirurgické výkony